CDT1 Is a Novel Prognostic and Predictive Biomarkers for Hepatocellular Carcinoma - Cai, Chenhui; Zhang, Ying; Hu, Xu; Hu, Wenhui; Yang, Sizhen; Qiu, Hao; Chu, Tongwei (Frontiers in Oncology, 2021)
Objective: Hepatocellular carcinoma (HCC) is known as one of the most common malignant tumors that endanger human health and life in the 21st century. Chromatin licensing and DNA replication factor 1 (CDT1) is an important regulator of replication licensing, which is essential for the initiation of DNA replication. CDT1 overexpression in several human cancers has been previously reported to leads to abnormal cell replication, activate DNA damage checkpoints, and predisposes for malignant transformation. However, the abnormal expression of CDT1 in HCC and its diagnostic and prognostic value remains to be clarified. Methods: TCGA, ONCOMINE, UALCAN, HCCDB, HPA, Kaplan-Meier plotter, STRING, GEPIA, GeneMANIA, ENCORI, TarBase, and TIMER were conducted for bioinformatics analysis. qRT-PCR and western blot were utilized for in vitro experiments. Results: We discovered the remarkably upregulated transcripts of CDT1 in HCC samples relative to normal liver samples through bioinformatics analysis and experimental verification in vitro. Moreover, in HCC patients, the transcriptional level of CDT1 was positively associated with clinical parameters such as the clinical stage of tumor. Survival analysis, logistic regression analysis, and Cox regression analysis showed the significant clinical prognostic significance of CDT1 expression in HCC. The received operating characteristic (ROC) curve and nomogram analysis results demonstrated a strong predictive ability of CDT1 for HCC. The Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene set enrichment analysis (GSEA) enrichment analyses showed that CDT1 was mainly related to the cell cycle, DNA repair, and DNA replication. We further demonstrated the significant correlation between CDT1 and MCM family genes and found the abnormal expression and prognostic significance of MCMs in HCC. Through multiple screening, we concluded that the key miRNAs involved in the negative regulation of CDT1 included hsa-miR-204-5p, hsa-miR-30e-5p, and hsa-miR-195-5p. Finally, immune infiltration analysis indicated that CDT1 was significantly associated with immune cell subsets and affected the survival of HCC patients. Conclusions: Our results systematically demonstrated the potential diagnostic and prognostic significance of CDT1 expression in HCC, as well as elucidated its potential molecular mechanism of promoting the occurrence and development of liver cancer, which may provide new opportunities and research direction for targeted therapies in HCC.